2008
DOI: 10.1016/j.ygeno.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression changes in children with autism

Abstract: The objective of this study was to identify gene expression differences in blood differences in children with autism (AU) and autism spectrum disorder (ASD) compared to general population controls. Transcriptional profiles were compared with age- and gender-matched, typically developing children from the general population (GP). The AU group was subdivided based on a history of developmental regression (A-R) or a history of early onset (A-E without regression). Total RNA from blood was processed on human Affym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(127 citation statements)
references
References 87 publications
5
119
0
1
Order By: Relevance
“…For example, a number of studies have suggested the involvement of genetic factors influencing immune function in the etiology of ASD (Gregg et al, 2008;Voineagu et al, 2011). It is possible that such genetic involvement may act as a confounder (the genetic factor increases risk of both infection and ASD, resulting in a spurious association between infection and ASD) or as an instrument (the genetic factor increases risk of infection which then increases risk of ASD) or as an effect modifier (the genetic factor amplifies the deleterious effect of infection on risk of ASD) -but the latter two does not change the result that maternal infection is associated with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a number of studies have suggested the involvement of genetic factors influencing immune function in the etiology of ASD (Gregg et al, 2008;Voineagu et al, 2011). It is possible that such genetic involvement may act as a confounder (the genetic factor increases risk of both infection and ASD, resulting in a spurious association between infection and ASD) or as an instrument (the genetic factor increases risk of infection which then increases risk of ASD) or as an effect modifier (the genetic factor amplifies the deleterious effect of infection on risk of ASD) -but the latter two does not change the result that maternal infection is associated with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these genes showed increased variability in the autism cohort, which suggests a general dysregulation of the autistic immune system and overall heterogeneous activation response. Another 2008 study identified 11 genes that were differentially expressed in children with autism, as well as within the subsets of early onset and developmental regression, as compared with the general population (overexpression in autism samples were confirmed for seven of 11 via qPCR) (Gregg et al, 2008). These genes are heavily overrepresented in the ontological KEGG natural killer cytotoxicity pathway, and are highly expressed in NK and CD8 T cells.…”
Section: Immunogenetic Factorsmentioning
confidence: 99%
“…A significant focus of the postnatal immune imbalance has been on specific immune cell subsets, including helper CD4 + and cytotoxic CD8 + T cells (Garbett et al, 2008;Gregg et al, 2008), which may behave differently in individuals with autism (Gupta et al, 1998). A 1986 study found a reduced number of T cells in individuals with autism, as well as an altered helper to suppressor T-cell ratio (Warren et al, 1986), while a supporting 1990 study suggested CD4 + cell levels were decreased in autism (Yonk et al, 1990).…”
Section: Immune Dysregulationmentioning
confidence: 99%
“…The characteristics of studies included in this analysis are listed in Table 1 (Nishimura et al, 2007;Gregg et al, 2008;Hu et al, 2009a,b;Alter et al, 2011;Voineagu et al, 2011;Kuwano et al, 2011;Ginsberg et al, 2012). The data sets for GSE30573 and GSE28521 were examined in the same study, but GSE30573 was RNA -seqdata set, and the data sets we applied were almost microarray data sets except for GSE30573.…”
Section: Overview Of the Studies Includedmentioning
confidence: 99%